THE EFFECT OF TEACHER'S PEDAGOGIC COMPETENCE ON STUDENT'S LEARNING ACHIEVEMENT IN IPS LEARNING DURING THE COVID-19 PANDEMIC IN CLASS V SDN 015 KENANGAN, LARIANG DISTRICT - Komang Sri Wiriyani; Surahman Surahman (Universitas Tadulako, 2021)
The purpose of this study was to determine the pedagogic competence of teachers and student achievement in social studies learning and the effect of teacher pedagogic competence on student achievement in social studies learning. This research method uses quantitative descriptive type with the research subjects are all fifthgrade students at SDN 015 Kenangan, Lariang District, amounting to 9 people. The results showed that of the 9 students, there were 9 students or 99.9% who stated that the teacher's pedagogical competence was good. While the student achievement of 9 students, there were 9 students or 99.9% who had good learning achievement. To determine whether there is an effect of teacher pedagogical competence with student achievement in social studies learning, it is consulted at a significant level of 5% or 0.05 (two nails) with the testing criteria if rcount <rtable, then Ho (null hypothesis) is rejected and if rcount> r_ (table,) then Ha (alternative hypothesis) is accepted. Based on the data found in this study, that the correlational analysis consulted at a significant level of 5% obtained r count> r table or 0.983> 0.666. This means that Ha (alternative hypothesis) is accepted and Ho (null hypothesis) is rejected. So it can be concluded that there is a positive and significant influence between teacher pedagogical competence and student achievement in social studies learning during the COVID-19 pandemic in Class V SDN 015 Kenangan, Lariang District